Anaerobic critical velocity in four swimming techniques - Neiva, H. P.; Fernandes, R. J.; Vilas-Boas, J. P. (International Journal of Sports Medicine, 2011)
The aim of this study was to assess critical velocity in order to control and evaluate anaerobic swimming training. 51 highly trained male swimmers performed maximal 15, 25, 37.5 and 50 m in the 4 swimming techniques to determine critical velocity from the distance-time relationship. Anaerobic critical velocity was compared with 100 m swimming performance and corresponding partials. Complementarily, 9 swimmers performed a 6×50 m (4 min interval) training series at front crawl individual anaerobic critical velocity, capillary blood lactate concentrations being assessed after each repetition. The mean±SD values of anaerobic critical velocity and its relationship with the 100 m event were: 1.61±0.07 (r=0.60, p=0.037), 1.53±0.05 (r=0.81, p=0.015), 1.33±0.05 (r=0.83, p=0.002), and 1.75±0.05 (r=0.74, p=0.001), for butterfly, backstroke, breaststroke and front crawl, respectively. However, differences between anaerobic critical velocity and performance were observed (with exception of the second half of the 100 m swimming events in breaststroke and butterfly). Lactate concentration values at the end of the series were 14.52±1.06 mmol.l-1, which suggests that it was indeed an anaerobic training set. In this sense, anaerobic critical velocity can be used to prescribe anaerobic training intensities.